2002
DOI: 10.1007/s11664-002-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack-growth behavior of Sn-Ag-Cu and Sn-Ag-Cu-Bi lead-free solders

Abstract: INTRODUCTIONLead-free solder alloys are intended to completely substitute for traditional Pb-Sn compositions in conventional processes in the future. Among them, tinsilver eutectic solder is an attractive candidate alloy for meeting the requirements for demanding hightemperature service environments, such as automotive applications. 1 However, Sn-Ag eutectic has a higher melting temperature and poorer wettability compared to Sn-Pb eutectic. 2 To improve the properties and decrease the melting temperature, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…[1] Given the technological need, there is an increasing body of published research on the creep of high-Sn alloys. [2][3][4][5][6][7] However, most of this work describes the creep of the alloys in bulk form. Solders in microelectronic joints may have microstructures and, hence, mechanical properties that differ significantly from those found in bulk samples.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Given the technological need, there is an increasing body of published research on the creep of high-Sn alloys. [2][3][4][5][6][7] However, most of this work describes the creep of the alloys in bulk form. Solders in microelectronic joints may have microstructures and, hence, mechanical properties that differ significantly from those found in bulk samples.…”
Section: Introductionmentioning
confidence: 99%
“…This will increase the operational reliability of PV module interconnections especially in the tropics. It has also been reported that interconnection degradation contributes to increase in series resistance of PV modules which decreases their power output [126], [137], [138], [141], [145]. …”
Section: Interconnection Technologiesmentioning
confidence: 99%
“…Currently, there is a shift from lead-based alloys to lead-free alloys because of the environmental impacts of lead, globally [144], [65], [148], [149]. More and more lead-free solders are being developed to substitute lead based solders [141], [142], [150]- [152]. The tin-silver-copper (SnAgCu or SAC) solder alloys have been reported to be the best alternative for eutectic SnPb solder in the PV industry [144], [153].…”
Section: Lead Free Soldermentioning
confidence: 99%
“…Since the use of lead solders in electronic devices is strictly restricted by the RoHS and WEEE legislation, most of lead solders have been replacing with lead-free solders. For seeking suitable lead-free solders, mechanical properties of lead-free solders have been actively investigated (3)- (12) as well as the other performance of the solders.…”
Section: Introductionmentioning
confidence: 99%